MONITORING OF PHYSICAL THERAPIST IN PREGNANT WOMEN IN THE DELIVERY ROOM (Fiep Bulletin - online, 2012)
This study is an update of the actions of physiotherapy in the delivery room. It will examine the key features of physiotherapy intervention adopted to decrease the time of labor, fear, tension and pain. The main focus of this review article has been monitoring the obstetric physiotherapist in pregnant women in delivery rooms, the techniques used during labor and the benefits that are obtained with these techniques when applied. The role of physiotherapy in this process is important because this professional is qualified to work in care for pregnant women, improving conditions of labor and humanizing the process even more.
Keywords: Monitoring of the physical therapist; childbirth; exercise.